The use of GeoGebra in a virtual learning environment (Research, Society and Development, 2018)
This article has the objective demonstrate preparation of a lesson using GeoGebra in a virtual learning environment to facilitate mathematical learning. For the GeoGebra installation, was demonstrated step by step, the transmission of the file produced by the teacher to the internet and the necessary settings in an AVA, with subsequent publication and release of the lesson to the student. The results of the process indicate the possibility of improvement in mathematical learning dynamically with punctual interactions. The presented format allows the insertion of activities in the mathematics discipline as an alternative to the traditional methodology, interacting with practical activities to the curricular component. The study in a virtual classroom, besides allowing the flexibility in learning, facilitates the student the exploration of the content, with associations, directed activities and researches for innovations, favoring the process of learning.